Structural basis of the broadly neutralizing anti‐interferon‐α antibody rontalizumab. (18th August 2015) - Maurer, Brigitte; Bosanac, Ivan; Shia, Steven; Kwong, Mandy; Corpuz, Racquel; Vandlen, Richard; Schmidt, Kerstin; Eigenbrot, Charles
Abstract Interferons‐alpha (IFN‐α) are the expressed gene products comprising thirteen type I interferons with protein pairwise sequence similarities in the 77–96% range. Three other widely expressed human type I interferons, IFN‐β, IFN‐κ and IFN‐ω have sequences 29–33%, 29–32% and 56–60% similar to the IFN‐αs, respectively. Type I interferons act on immune cells by producing subtly different immune‐modulatory effects upon binding to the extracellular domains of a heterodimeric cell‐surface receptor composed of IFNAR1 and IFNAR2, most notably anti‐viral effects. IFN‐α has been used to treat infection by hepatitis‐virus type C (HCV) and a correlation between hyperactivity of IFN‐α‐induced signaling and systemic lupus erythematosis (SLE), or lupus, has been noted. Anti‐IFN‐α antibodies including rontalizumab have been under clinical study for the treatment of lupus. To better understand the rontalizumab mechanism of action and specificity, we determined the X‐ray crystal structure of the Fab fragment of rontalizumab bound to human IFN‐α2 at 3Å resolution and find substantial overlap of the antibody and IFNA2 epitopes on IFN‐α2.